2003
DOI: 10.1186/1477-7525-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Functional Assessment of Chronic Illness Therapy (FACIT) Measurement System is a collection of health-related quality of life (HRQOL) questionnaires targeted to the management of chronic illness. The measurement system, under development since 1987, began with the creation of a generic CORE questionnaire called the Functional Assessment of Cancer Therapy-General (FACT-G). The FACT-G (now in Version 4) is a 27-item compilation of general questions divided into four primary QOL domains: Physical Well-Being, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
487
1
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,193 publications
(504 citation statements)
references
References 28 publications
(4 reference statements)
5
487
1
11
Order By: Relevance
“…Evidence supported test-retest reliability, as well as convergent and divergent validity (Brady et al, 1997;Cella et al, 1993;Overcash et al, 2001;Webster et al, 2003;Webster et al, 1999;Winstead-Fry & Schultz, 1997). For the purpose of the present investigation, the five subscales and the Devins, 1990).…”
Section: Socio-demographic Variablessupporting
confidence: 51%
See 1 more Smart Citation
“…Evidence supported test-retest reliability, as well as convergent and divergent validity (Brady et al, 1997;Cella et al, 1993;Overcash et al, 2001;Webster et al, 2003;Webster et al, 1999;Winstead-Fry & Schultz, 1997). For the purpose of the present investigation, the five subscales and the Devins, 1990).…”
Section: Socio-demographic Variablessupporting
confidence: 51%
“…The FACT-B has been extensively used in psychosocial oncology research and has demonstrated to have high validity and internal consistency (Brady et al, 1997;Cella et al, 1993;Overcash, Extermann, Parr, Perry, & Balducci, 2001;Webster, Cella & Yost, 2003;Webster, Odom, Peterman, Lent, & Cella, 1999;Winstead-Fry & Schultz, 1997).…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
“…Aunque existen herramientas para valorar múltiples expresiones de la EC tales como el dolor [24,25], La funcionalidad [26,27], el autoconcepto [28], la relación entre aspectos biológicos y psicológicos (29,30), la condición espiritual (31), la capacidad de descansar [32,33], la situación económica [34,35], e incluso el nivel de apoyo social que el paciente recibe junto con su cuidador (36), hay también evidencia de que muchos de los síntomas y quejas del paciente con EC se quedan sin valorar [37] y que la valoración quizá por ello se ha enfatizado en la necesidad de tener en cuenta la perspectiva subjetiva del paciente [38], con base en la cual se abren importantes posibilidades para el cuidado de su salud [39].…”
Section: Discussionunclassified
“…Symptom burden was self-reported using the COPD Assessment Test [21] and usual modified Medical Research Council dyspnea grade [22]. Fatigue was self-reported using Functional Assessment of Chronic Illness Therapy-Fatigue with a score <30 indicating severe fatigue [23]. Anxiety and depression were examined using the Hospital Anxiety and Depression Scale [24] with a normal score considered as 0 to 7, borderline abnormal level considered 8 to 10, and abnormally high anxiety/depression considered 11 to 21 [25].…”
Section: Sample Descriptive Measuresmentioning
confidence: 99%